Foundations of financial management - Block, Stanley B. (Irwin, 1997)
Includes electronic study questions that contain glossary terms, chapter outlines, chapter summaries, and true-false and multiple-choice questions for each chapter. It enables students to take a test from one chapter or several chapters at a time. It also has a Time Value of Money problem generator that creates an infinite number of problems for review. Excel Templates are also included. The software is written by the authors.